Specialized functions of the PP2A subfamily II catalytic subunits PP2A‐C3 and PP2A‐C4 in the distribution of auxin fluxes and development in Arabidopsis. (17th January 2013) - Ballesteros, Isabel; Domínguez, Teresa; Sauer, Michael; Paredes, Pilar; Duprat, Anne; Rojo, Enrique; Sanmartín, Maite; Sánchez‐Serrano, Jose J.
Summary: Protein phosphorylation is a key molecular switch used to transmit information in biological signalling networks. The output of these signalling circuits is governed by the counteracting activities of protein kinases and phosphatases that determine the direction of the switch. Whereas many kinases have been functionally characterized, it has been difficult to ascribe precise cellular roles to plant phosphatases, which are encoded by enlarged gene families that may provide a high degree of genetic redundancy. In this work we have analysed the role in planta of catalytic subunits of protein phosphatase 2A (PP2A), a family encoded by five genes in Arabidopsis. Our results indicate that the two members of subfamily II, PP2A‐C3 and PP2A‐C4, have redundant functions in controlling embryo patterning and root development, processes that depend on auxin fluxes. Moreover, polarity of the auxin efflux carrier PIN1 and auxin distribution, determined with the DR5 pro :GFP proxy, are affected by mutations in PP2A‐C3 and PP2A‐C4 . Previous characterization of mutants in putative PP2A regulatory subunits had established a link between this class of phosphatases and PIN dephosphorylation and subcellular distribution. Building on those findings, the results presented here suggest that PP2A‐C3 and PP2A‐C4 catalyse this reaction and contribute critically to the establishment of auxin gradients for proper plant development.